PENGARUH PERCEIVED EASE OF USE, PERCEIVED USEFULNESS, DAN PERCEIVED RISK TERHADAP INTENTION TO TRANSACT PADA TOKO ONLINE DI SURABAYA - SUTOMO, DEVI (Kajian Ilmiah Mahasiswa Manajemen, 2012)
The purpose of this research is knowing the effect perceived ease of use on perceived usefulness, the effect perceived ease of use on intention to transact, the effect perceived usefulness on intention to Transact, the effect perceived risk on intention to transact and the effect perceived ease of use on the intention to transact through perceived usefulness at the online shop in Surabaya. Amount samples in this study is 150 samples. Data analysis technique used is a Structural Equation Model (SEM) with LISREL 8.70 program. The results of this study indicate that perceived ease of use has a positive effect on perceived usefulness, perceived ease of use has a positive effect on intention to transact, perceived usefulness has a positive effect on intention to transact, perceived risk has a negative effect on intention to transact and perceived ease of use has a positive effect on intention to transact through perceived usefulness.